Comparative study of the life cycle assessment of particleboards made of residues from sugarcane bagasse (Saccharum spp.) and pine wood shavings (Pinus elliottii) - dos Santos, Maria Fernanda N.; Battistelle, Rosane Ap. G.; Bezerra, Barbara Stolte; Varum, Humberto S.A. (Elsevier, 2013)
This paper presents a research on the environmental impacts of particleboards produced from wastes, based on a comparative Life Cycle Assessment study. The particleboards were manufactured in laboratorial scale from the following residues: sugarcane bagasse (Saccharum spp.) and pine wood shavings (Pinus elliottii). The study was developed following the methodological guidelines of ISO 14040. The functional unit adopted was the m2 of the particleboards produced and the impacts were evaluated by the Environmental Development of Industrial Products method. The results indicated that pine particleboard present the highest environmental impact potential. Our findings suggested that the factors that mostly aggravated the environmental impacts were: the distance between the raw materials and the production site, and formaldehyde emissions (FE). The first is related to the combustion of fossil fuel during the acquisition of raw material, which achieved the values of 2185.94 g/m2 for consumption of non-renewable resources for pine particleboard and 893.53 g/m2 for bagasse particleboard. The second is related to the use of urea-formaldehyde resin, responsible for the FE into the air during production. The FE is accountable for the contamination of approximately 7,800,000.00 m3 of air per m2 of particleboard produced, and was the factor with the greatest impact in human toxicity potential. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Civil construction; Life Cycle Assessment; Particleboards; Production prevention